2006
DOI: 10.1111/j.1471-0528.2006.00882.x
|View full text |Cite
|
Sign up to set email alerts
|

Maternal medicine: Morphometric placental villous and vascular abnormalities in early‐ and late‐onset pre‐eclampsia with and without fetal growth restriction

Abstract: Objective To evaluate placental morphology in pregnancies complicated by early-and late-onset pre-eclampsia (PET) with and without fetal growth restriction (FGR) using stereological techniques.Design A total of 69 pregnant women were studied. Twenty women had pregnancies complicated by PET, 17 by FGR and 16 by both PET and FUR; the remaining 16 were from gestationalage-matched controls. Each group was further classified into early onset (<34 weeks) and late onsets (>34 weeks) based on gestational ages.Setting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
209
4
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 333 publications
(231 citation statements)
references
References 56 publications
17
209
4
1
Order By: Relevance
“…[22][23][24][25][26] It has also been suggested that women with chronic hypertension or diabetes mellitus develop PE in the context of smaller increments of sFlt and sEng, because there is already preexisting maternal endothelial cell dysfunction. 27 Our finding of more significant alterations in angiogenic factors in early versus late-onset SPE are consistent with reports that more severe placental dysfunction distinguishes early onset from late-onset SPE in women without preexisting hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…[22][23][24][25][26] It has also been suggested that women with chronic hypertension or diabetes mellitus develop PE in the context of smaller increments of sFlt and sEng, because there is already preexisting maternal endothelial cell dysfunction. 27 Our finding of more significant alterations in angiogenic factors in early versus late-onset SPE are consistent with reports that more severe placental dysfunction distinguishes early onset from late-onset SPE in women without preexisting hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 The underlying mechanism for early-PE, requiring delivery before 34 weeks, is thought to be impaired placentation because of inadequate trophoblastic invasion of the maternal spiral arteries, which has been documented by the findings of both histologic and Doppler ultrasound studies of the uterine arteries, [3][4][5][6][7][8] reduced maternal serum concentration of the placental product pregnancy-associated plasma protein-A (PAPP-A) 9 and impaired fetal growth. 10 In contrast late-PE, which is usually associated with normal placentation and fetal growth, 11,12 is thought to be a manifestation of an underlying metabolic disorder with increased insulin resistance. [13][14][15] Insulin-like growth factor-binding protein 3 (IGFBP-3) belongs to the family of IGFBPs, which determine the bioavailability and activity of the IGFs.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, microarray analysis has described the lower expression of at least two angiogenesis-associated transcripts (Egfl7 and Acvrl1) in EOPE compared to LOPE or agematched controls [15]. Therefore, reduced placental angiogenesis could be responsible for the impaired placental blood flow observed in EOPE, while the observed normal blood flow in LOPE could result from either no alterations or increased placental angiogenesis [3,6,13].…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, Doppler studies reveal that impaired feto-placental blood flow is mainly evident in women with early-onset preeclampsia (EOPE) [8] rather than late-onset preeclampsia (LOPE) [9]. Moreover, EOPE exhibits placental histological changes related with reduced perfusion [10][11][12][13] as well as the anomalous structure of the peripheral villi and vasculature compared to respective controls identified by stereological analysis following EOPE, but not LOPE [13]. In addition, low placental levels of several pro-angiogenic factors have been reported in EOPE compared to LOPE or age-matched controls [14,15].…”
Section: Introductionmentioning
confidence: 99%